Scientific production of the journal Odontología Sanmarquina in the period 2015-2020, a bibliometric analysis - Castro-Rodríguez, Yuri (2021)
Objective. To describe the scientific production of the journal Odontología Sanmarquina (OS) during 2015-2020 period. Methods. Descriptive study of bibliometric design that used the articles published in the journal OS as the object of study. The bibliometric indicators included: productivity per year, type of publications, student authorship, and subject of the studies, quantity, academic degree and nationality of the authors, international collaboration and affiliation in authorship. Absolute and relative frequencies were used to summarize the findings, as well as comparative tables between variables. Results. Two hundred forty-one articles published during a period of six years were analyzed, 37.8% corresponded to original articles, 20.7% to clinical reports and 15.4% to bibliographic reviews. The most prevalent topics in the studies were those related to Medicine and Stomatological Pathology (19.9%) and Dental education (19.1%); 6.2% of the publications had student authorship. The foreign countries with the highest frequency were Mexico (9%), Chile (9%) and Brazil (7%). Conclusions. The OS magazine presents a constant publication, which has increased since 2015, presenting national and international authors. The largest number of publications are original articles and clinical cases reports. The most frequent topics are related to Medicine and Stomatological Pathology. There is a high predominance of Peruvian authors as well as a limited participation of undergraduate students in the authorship of the articles.